1999
DOI: 10.1080/00221329909595403
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neonates' Cuddliness

Abstract: The authors undertook the present study to determine whether under ecologically valid, low-stress conditions, female and male neonates could be differentiated on cuddliness. Sixteen female and 15 male neonates were videotaped interacting briefly with both a female and a male adult who were blind to the sex of the neonate. Raters coded degree of cuddliness and activity level. Results showed that raters could discriminate the sex of the neonate on the basis of degree of cuddliness. Discussion focuses on the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This result is consistent with Gunnar, Porter, Wolf, Rigatuso, and Larson (1995) who also reported higher parental ratings of Distress to Limitations for boys compared to girls at 6 months. There is evidence that already as neonates, girls show a greater degree of cuddliness than boys (Benenson, Philippoussis, & Leeb, 1999). In the current study, this difference was only found at 12 months but not at 6 months of age.…”
Section: Infant Gendermentioning
confidence: 94%
“…This result is consistent with Gunnar, Porter, Wolf, Rigatuso, and Larson (1995) who also reported higher parental ratings of Distress to Limitations for boys compared to girls at 6 months. There is evidence that already as neonates, girls show a greater degree of cuddliness than boys (Benenson, Philippoussis, & Leeb, 1999). In the current study, this difference was only found at 12 months but not at 6 months of age.…”
Section: Infant Gendermentioning
confidence: 94%
“…One suggestion is that biological influences associated with the sexual differentiation of behavior should have no direct effects on basic or sensory processes associated with infant survival (Benenson, Philippoussis, & Leeb, 1999). Yet, one recent explanation for the greater infant mortality and complication rates in males is that exposure to higher prenatal androgen levels enhances fetal growth and inhibits lung development (Mage & Donner, 2006).…”
Section: Basic and Sensory Processesmentioning
confidence: 99%
“…Infant girls may also show greater responsiveness to social stimuli, such as the maternal face, sound, or touch. For example, compared to males, female newborns score higher in global ratings of cuddliness (Benenson et al, 1999), show more orientation to a face or voice (Connellan, Baron-Cohen, Wheelwright, Batki, & Ahluwalia, 2000;Osofsky & O'Connell, 1977), and, like older infant girls (Mundy et al, 2007), exhibit longer eye contact with an experimenter (Hittelman & Dickes, 1979). Sex differences in the incentive value of social stimuli are also consistent with findings that infant girls show stronger visual preferences for a doll (i.e., an object with human attributes) than for a toy truck (Alexander, Wilcox, & Woods, 2009) than infant boys.…”
Section: Social Behaviormentioning
confidence: 99%
“…Even newborns display a difference in "thing versus people" orientation, with girls attending more to human faces and boys paying more attention to moving objects (Connellan et al 2000), and newborn girls are measurably more "cuddly" than boys (Benenson et al 1999). Many differences appear early in life, before a child has had an opportunity to absorb social expectations of sex-appropriate behavior.…”
Section: Activational Effectsmentioning
confidence: 99%